Practitioners' perspectives on in-house versus arm's-length structures of local economic development delivery in Ontario, Canada. Issue 6 (2nd November 2019) - Buttazzoni, Adrian; Arku, Godwin; Cleave, Evan
ABSTRACT: The structure for local economic development is an important part of the development process. In recent years, local governments have been switching structures, leading to debates about the most appropriate structure for an effective economic development delivery. Based on in-depth interviews with practitioners of local economic development, the paper examines the strengths and drawbacks of the two primary structures in the Province of Ontario: In-house and Arms-length. In doing so, the paper accomplishes two things: first, it adds to the empirical discussion on organisational approaches to economic development; second, it provides an informed perspective to assist communities that might be considering switching their structures.